Absorção de N, P, K, ca E Mg por laranjeiras 'pêra' fertilizadas com lodo de esgoto compostado em substituição à adubação nitrogenada mineral - Romeiro, Júlio Ćsar Thoaldo; Grassi Filho, Hélio [UNESP]; Moreira, Lais Lorena Queiroz [UNESP] (My University, 2014)
The objective of the study was to evaluate leaf levels of N, P, K, Ca and Mg in orange trees as a function of different levels of composted sewage sludge to replace mineral N fertilization. For dose calculation, 2.77% N in the residue and 30% mineralization rate were considered. Doses consisted of 0, 6, 12, 18, 24 and 30 kg plant-1 of sewage sludge which were supplemented with mineral sources to meet 100% nutritional demand. Plants were grown in 500 L soil pots and drip irrigated to replace evapotranspirated water from the day before. The use of composted sewage sludge in soil for fertilization of Pear orange trees had significant effects on leaf levels of N, P and Ca. Doses higher than 18 kg sludge plant-1 in the treatments caused a nutritional imbalance between Ca and Mg, and adversely affected Mg uptake, which showed leaf levels with lower levels of Mg when compared with those considered as appropriate.
Uptake of N, P, K, ca and mg by 'pear' orange trees fertilized with composted sewage sludge to replace mineral nitrogen fertilization
Keywords: Citrus sinensis; Composted sewage sludge; Nitrogen